Linkage of Higher Education Competencies with Job Readiness: Case Study of Economics and Business Graduates - Moh Yudi Mahadianto; Muhammad Irvan; Qotrunnada Salsabila; M Septian Arya Permana (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Work readiness is a critical priority for higher education institutions as they strive to align graduate competencies with the evolving demands of the labor market. This study explores the relationship between generic and specific competencies developed through higher education and their influence on the employability of economics and business graduates. Employing a systematic literature review, the research identifies key gaps between employer expectations and the competencies imparted by higher education institutions. Generic competencies—such as critical thinking, teamwork, communication, and problem-solving—are found to enhance workplace adaptability, while specific competencies, including technical skills and domain-specific knowledge, directly contribute to job performance and operational efficiency. The study underscores the role of targeted training programs, such as Professional Project Manager Training and Brevet Tax Training, alongside professional certifications like Certified Accurate Professional (CAP) and Associate Certified Public Accountant (ACPA), in bridging these competency gaps. Recommendations include embedding industry-relevant skills into academic curricula, strengthening collaborations between academia and industry, and promoting continuous professional development initiatives to enhance graduate readiness for the labor market. This research contributes to the discourse on employability by offering actionable insights for higher education institutions and policymakers aiming to close competency gaps. While the study is limited by its reliance on secondary data and focus on specific sectors, future research should prioritize empirical data collection and cross-sectoral analyses to validate and expand upon these findings.